Platelets, alcohol consumption, and onset of brain infarction. Issue 4 (October 1996) - Numminen, H; Hillbom, M; Juvela, S
Abstract : OBJECTIVES: Previous investigations have suggested that recurrent rebound thrombocytosis after alcohol misuse may be a factor in the pathogenesis of thromboembolic disease. Alcohol consumption, platelet count, and platelet function were examined among patients of working age with brain infarction. METHODS: Platelet count and risk factors for stroke were studied in 426 stroke patients and 157 control patients in hospital. The measures were platelet count obtained within four days after the stroke onset, in vitro adenosine diphosphate induced platelet aggregation, associated thromboxane B2 formation, and urinary excretion of 11-dehydrothromboxane B2. RESULTS: After adjustment for sex, age, cardiac disease, diabetes, and alcohol intake, hypertension (OR 3.4, 95% confidence interval (95% CI) 2.0-6.0) and current smoking (OR 2.1, 95% CI 1.4-3.3) were associated with an increased risk for brain infarction. Platelet count shortly after the onset of disease was higher in the stroke patients than in the controls (OR 1.05/10(10)/1 platelets; 95% CI 1.02-1.09). The patients with brain infarction who were heavy alcohol drinkers (n = 144) showed both thrombocytosis (OR 2.30, 95% CI 0.82-6.44) and thrombocytopenia (OR 3.20, 95% CI 1.19 to 8.59) more often at the onset of the stroke than the other patients with brain infarction. The thromboxane variables showed inconsistent associations with the onset of stroke. There was no consistent platelet abnormality among alcohol misusers at the onset of ischaemic brain infarction. CONCLUSIONS: Alcohol induced thrombocytopenia and rebound thrombocytosis were both often seen at the onset of brain infarction in patients who were heavy alcohol drinkers. Therefore, other mechanisms which could contribute to the high frequency of recurrences of ischaemic stroke among heavy drinkers should be investigated.